Social Forestry in India - Kondas, S. (Indian Forester, 1985)
Forestry tradition had not been particularly strong in agriculturally oriented India. The issues of chronic scarcity of fuelwood and fodder and the necessity of raising village plantations were raised from time to time late 19th and early 20th centuries. Consequent to the National Forest Policy of 1952 emphasizing the necessity of a third of the land area remaining under forests a concerted move was made in the sixties to expand tree lands outside State forests. Although some beginning was made large scale programmes with the support of foreign aid agencies were launched in the eighties only. The criticism and constraints in the implementation are analysed. Considering the magnitude and complexity of the Programme it is obvious that further implementation will hinge heavily on the good organizational infrastructure namely the Panchayats, Cooperatives and village school developed during the passage of six Five Year Plans. The huge unmet demand for fuelwood and fodder will place a premium on the price of wood for many years to come and this should sustain the tempo of the Programme. In the context of Social Forestry, wastelands and marginal lands of problems and low productivity are often thought of. In addition to these lands, agricultural lands aggregating 143 m ha (43.5% of total land area) particulary the underutilized irrigated lands of 68 m ha should be seriously thought of for gainful social forestry.